2021
DOI: 10.1186/s43045-021-00094-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing COVID19-related anxiety in an Egyptian sample and correlating it to knowledge and stigma about the virus

Abstract: Background COVID19 public health crisis has led to extensive anxiety regarding spread of virus. Aim of study is to assess COVID19-related anxiety in Egypt and correlate it to knowledge and stigma. Results Online questionnaire, 17–20 April 2020, had 218 Egyptian respondents to a socio-demographic questionnaire and Generalized Anxiety Disorder Scale (GAD-7). The present study revealed that 21.2% of the respondents were experiencing severe anxiety, 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…For example, in China, different studies have reported moderate to severe anxiety symptoms (e.g., fear, worry, apprehension) which vary between 14% and 53% among teachers (Huang and Zhao 2020;Li et al 2020aLi et al , 2020bWang et al 2020Wang et al , 2021Xiong et al 2020). Similar prevalence rates and symptoms (e.g., worry, fear, depression) have also been reported in several studies across different regions such as Europe: France (Mary-Krause et al 2021); Germany (Weinert et al 2021); Italy (Gualano et al 2020); UK (Allen et al 2020;Dougall et al 2021); Spain (Prado-Gascó et al 2020), and in the US (Cipriano and Brackett 2020;Pressley et al 2021), as well as Africa (Fodjo et al 2021;Hafez and El-Din 2021;Ofori et al 2021;Ominde et al 2021;Rabei and Abd El Fatah 2021) among teachers.…”
Section: Introductionsupporting
confidence: 71%
“…For example, in China, different studies have reported moderate to severe anxiety symptoms (e.g., fear, worry, apprehension) which vary between 14% and 53% among teachers (Huang and Zhao 2020;Li et al 2020aLi et al , 2020bWang et al 2020Wang et al , 2021Xiong et al 2020). Similar prevalence rates and symptoms (e.g., worry, fear, depression) have also been reported in several studies across different regions such as Europe: France (Mary-Krause et al 2021); Germany (Weinert et al 2021); Italy (Gualano et al 2020); UK (Allen et al 2020;Dougall et al 2021); Spain (Prado-Gascó et al 2020), and in the US (Cipriano and Brackett 2020;Pressley et al 2021), as well as Africa (Fodjo et al 2021;Hafez and El-Din 2021;Ofori et al 2021;Ominde et al 2021;Rabei and Abd El Fatah 2021) among teachers.…”
Section: Introductionsupporting
confidence: 71%
“…Kemunculan dan penyebaran Covid-19 menimbulkan ketakutan yang menjadi tempat berkembang biaknya kebencian dan stigma.Stigma dapat membuat orang menyembunyikan penyakit mereka dan tidak segera mencari perawatan kesehatan.Meminimalkan stigma dapat dilakukan dengan memperkenalkan data secara profesional yang memahami keadaan emosi dan kebutuhan audiens.Dan saat menyikapi data publik disesuaikan dan ditampilkan secara jujur namun tetap dalam konteks yang meningkatkan baik pemecahan masalah maupun koping emosional masyarakat.Fakta epidemiologis yang jelas dan kuat dalam wabah untuk melawan ketidakpastian, desas-desus, dan spekulasi yang memicu kecemasan. Epidemiologi emosional menjadi salah satu target di era media sosial dengan umpan berbahaya yang terorganisir sebagai rumor, setengah kebenaran, dan berita palsu [18].…”
Section: Gambaran Stigma Masyarakat Terhadap Pandemi Covid-19 DI Indo...unclassified
“…The arrival of the COVID-19 pandemic represented a global public mental health crisis. Rates of anxiety, depression, and isolation increased [37,38]. Research identified several knowledge and behavioral factors as key mediators contributing to an individual's sense of well-being.…”
Section: Introductionmentioning
confidence: 99%